Cretaceous faunas from Zululand and Natal, South Africa. Systematic palaeontology and stratigraphical potential of the Upper Campanian-Maastrichtian lnoceramidae (Bivalvia) - Walaszczyk, I; Kennedy, W; Klinger, H (2009)
Thirty three species of Inoceramidae, of which two are new, are described from KwaZulu. They fall into four zonal assemblages that can be correlated with sequences recognized elsewhere: the Cataceramus flexus Zone and the 'Inoceramus' tenuilineatus Zone are referred to the lower Upper Campanian. The Trochoceramus radiosus Zone is referred to the upper Lower Maastrichtian. The 'Inoceramus' ianjonaensis Zone is referred to the lower Upper Maastrichtian, and represents the youngest known assemblage of true inoceramids. There is no evidence for upper Upper Campanian or lower Lower Maastrichtian inoceramids, and this, together with the geological context of the faunas, indicates the presence of a regional unconformity at this level. This is confirmed by the associated ammonite assemblages. The inoceramid faunas include many taxa that have a wide distribution in the northern hemisphere, and provide a basis for correlation with the ammonite and inoceramid zonations recognized in the U.S. Western Interior, and the European ammonite and belemnite succession.